Bi-objective optimisation of single-layer steel grid structures of folded-plate curtain walls. (November 2015) - Xiao, J. C.; Wei, X.; Luo, J.
Abstract : From the standpoint of project general contract, steel consumption is one of the most concerned indicators for the optimisation of single-layer steel grid structures of folded-plate curtain walls. Other objectives include construction period, processing difficulty, construction convenient, transportation cost and administrative expenses, etc. It is difficult to consider these indicators simultaneously. We use the number of cross-sections of members as a substitute for the secondary indicators by correlation analysis. A weight function is introduced to consider the influence of the number of cross-sections of members on steel consumption on the basis of construction cost statistics and analytical hierarchy process. The optimal solution is determined by comparing the composite indicators. There is a slight difference between bi-objective optimisation and single-objective problem in the case study.